OKU digital hub information / Irfan Zainuddin - Zainuddin, Irfan (Faculty of Art and Design, 2020)
Workplace nowadays are moving into the era of 'Internet of Things'. One of the causes to the problem is parents and teachers are still lack of knowledge on how to get possibilities & facilities provided by government and private sector for their children.